2022
DOI: 10.1111/1471-0307.12911
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular mechanisms of novel antioxidative peptides from fermented camel milk (Kachchi breed, India) with anti‐inflammatory activity in raw macrophages cell lines

Abstract: The investigation was aimed at assessing anti‐inflammatory and antioxidative activities along with the release of peptides with antioxidative properties during the fermentation of camel milk by Lacticaseibacillus casei (NK9). Reverse‐phase high‐performance liquid chromatography (RP‐HPLC) was used to separate the bioactive peptides of 3 and 10 kDa (permeates and retentates). Reverse‐phase liquid chromatography–mass spectrometry (RPLC/MS) was used to identify and characterise the pure bioactive peptides, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…TNF-α, IL-6, IL-1β, and NO were overproduced in this study as a result of LPS stimulation; however, buffalo and camel milk fermented with KGL4 + WBS2A dramatically reduced these levels. As to the reliability of our current figures, many earlier studies confirmed that different peptides could suppress NO production during inflammation [81][82][83]. These findings suggested that the extracts had anti-inflammatory effects by lowering NO synthesis in RAW 264.7 cells and that they might function as potent anti-inflammatory peptides when inflammation is present.…”
Section: Analysis Cytokine In Raw 2647 Cellssupporting
confidence: 77%
“…TNF-α, IL-6, IL-1β, and NO were overproduced in this study as a result of LPS stimulation; however, buffalo and camel milk fermented with KGL4 + WBS2A dramatically reduced these levels. As to the reliability of our current figures, many earlier studies confirmed that different peptides could suppress NO production during inflammation [81][82][83]. These findings suggested that the extracts had anti-inflammatory effects by lowering NO synthesis in RAW 264.7 cells and that they might function as potent anti-inflammatory peptides when inflammation is present.…”
Section: Analysis Cytokine In Raw 2647 Cellssupporting
confidence: 77%
“…Furthermore, Dharmisthaben et al . (2022) study found two novel peptides, which are LLNEK and IYTFPQPQSL, released from camel milk fermented with Lacticaseibacillus casei (NK9) (5 × 10 8 cfu mL −1 ) at 37 °C for 24 h, showed remarkable anti‐inflammatory activity. Ashokbhai et al .…”
Section: Effect Of Proteolytic Fermentation On the Fermented Foodmentioning
confidence: 99%
“…Furthermore, Dharmisthaben et al (2022) study found two novel peptides, which are LLNEK and IYTFPQPQSL, released from camel milk fermented with Lacticaseibacillus casei (NK9) (5 9 10 8 cfu mL À1 ) at 37 °C for 24 h, showed remarkable antiinflammatory activity. Ashokbhai et al (2022) identified five novel antimicrobial peptides against Enterococcus faecalis, Salmonella typhimurium, B. cereus, and E. coli in sheep milk fermented with L. fermentum KGL at 48 h, including peptide FAWPQYLK.…”
Section: Effect On Biological Activitiesmentioning
confidence: 99%